Effectiveness of catechin extract of green tea (camellia sinensis) on porphyromonas gingivalis - Hendrastuti Handayani; Dekarini D. Putri; Fajriani; Sartini (DiscoverSys Inc., 2021)
Objective: To find out the effectiveness of catechin extract of green tea (Camellia sinensis) on Porphyromonas gingivalis. Material and Methods: The independent variables were catechin extracts of green tea (camellia sinensis) starting from the 40%, 20%, 10%, 5%, 2.5% and 1.2% concentrations. The dependent variables were the Minumum Inhibitory Concentration (MIC) and the Inhibition zone of bacterial growth of porphyromonas gingivalis. Control variables were time, culture medium, and temperature. The sample of research were Porphyromonas gingivalis which has been bred and catechin extract of green tea (camellia sinensis) that extracted by maceration method.Results: At the 40%, 20%, 10%, and 5% concentrations, the growth of Porphyromonas gingivalis did not change. As for the 2.5% and 1.25% concentrations, bacterial growth has occurred.Conclusion: Catechin extract of green tea (Camellia sinensis) was effective in inhibition of Porphyromonas gingivalis.